(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
The article provides data on the natural distribution of vitamin plants in Karakalpakstan and on the norms of their use and medicinal plants. Also about the preservation of vitamins in various plant organs, the daily requirement for human vitamins, taking into account the state of health and working conditions. Causes of body weakness, dry skin, brittle nails associated with a lack of beneficial vitamins.